2017
DOI: 10.1111/evj.12705
|View full text |Cite
|
Sign up to set email alerts
|

Head, withers and pelvic movement asymmetry and their relative timing in trot in racing Thoroughbreds in training

Abstract: SummaryBackgroundHorses show compensatory head movement in hindlimb lameness and compensatory pelvis movement in forelimb lameness but little is known about the relationship of withers movement symmetry with head and pelvic asymmetry in horses with naturally occurring gait asymmetries.ObjectivesTo document head, withers and pelvic movement asymmetry and timing differences in horses with naturally occurring gait asymmetries.Study designRetrospective analysis of gait data.MethodsHead, withers and pelvic movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 27 publications
(41 reference statements)
4
33
0
Order By: Relevance
“…) and that racing Thoroughbreds show these patterns (Pfau et al . ), we further (qualitatively) investigated the head‐withers movement asymmetry relationship.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…) and that racing Thoroughbreds show these patterns (Pfau et al . ), we further (qualitatively) investigated the head‐withers movement asymmetry relationship.…”
Section: Resultsmentioning
confidence: 99%
“…; Pfau et al . ). For qualitative comparison between visual assessment and quantitative asymmetry measurement, the side of lameness was defined from HDmin for forelimb lameness and PDmin for hindlimb lameness (based on previously identified associations with peak force asymmetry (Keegan et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…These extremes cause translational difficulties, in which stakeholders may be uncomfortable with the ‘black box’ element of the data analysis and interpretation – particularly automated interpretation of ‘normal’ or ‘abnormal’. Thresholding and categorising horses against population norms is no longer considered a worthy indicator of normality/abnormality . A recent review of induced lameness research suggested that we must anticipate that objective gait quantification techniques will become the monitoring standard in equine gait analysis .…”
Section: Existing and Potential Barriers To Advancing Researchmentioning
confidence: 99%
“…Its use in aiding lameness diagnosis and monitoring is mainly based on measuring gait asymmetries, determining whether those asymmetries are over pre-set thresholds and deciding on their clinical relevance. Much work has already been done to investigate symmetry and asymmetry values of the motion of various body parts (including vertical displacement of head, withers and pelvis; joint angle parameters of the limbs and vertebral column), stride parameters and limb loading; as well as the symmetry values seen under different conditions such as different disciplines, training, type of terrain, with or without a rider and during lungeing or when moving over a straight line [1][2][3][4][5][6][7]. Further refinement of knowledge on gait parameters is still warranted, and research in the area will not cease as technologies evolve.Although perfectly suited for the purpose, quantitative gait analysis has been used in very few studies of neurological conditions.…”
mentioning
confidence: 99%